2016
DOI: 10.1002/cam4.644
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of postdiagnosis platelet count with overall survival of pancreatic cancer: a counting process approach

Abstract: The association between long‐term variation of postdiagnosis platelets and survival of pancreatic cancer (PC) has never been discussed by using dynamic survival analysis method. In this retrospective study, we analyzed 311 histologically confirmed PC patients identified from a mega population‐based electronic inpatients database from 2012 to 2013 in China. Counting process approach was applied to restructure the original survival data, the association between post‐diagnosis platelet count and overall survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…A detailed description of this method can be found in Anderson and Gill’s work [17], and the analytical strategy of AG model in this study is provided in Appendix 1. Although time-dependent variables are ubiquitous in the field of cancer survival, the application of AG model is rare, only can be found in two previously published studies [18, 19].…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of this method can be found in Anderson and Gill’s work [17], and the analytical strategy of AG model in this study is provided in Appendix 1. Although time-dependent variables are ubiquitous in the field of cancer survival, the application of AG model is rare, only can be found in two previously published studies [18, 19].…”
Section: Methodsmentioning
confidence: 99%
“…5 However, the association between platelets and prognosis remains controversial. It was once believed that platelets in the blood circulation (ie, platelet count, platelet CRP multiplier value, plateletto-monocyte ratio and the platelet-to-albumin ratio) are related to poor clinical outcomes in patients with cancer, [6][7][8][9] but evidence also exists suggesting that the platelet count in the blood circulation does not correlate with prognosis. 10 In recent years, researchers have focused on immune cell infiltration and patient survival and have used the immune score to investigate the survival of patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…We only identified 2 newly published studies which discussed this association in advanced PC patients: one observed prominent association while the other did not. [ 15 , 17 ] However, these 2 studies all focused on general OS rather than short-term OS. From this point of view, our study is valuable in accumulating the initial evidence.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Our finding perhaps suggested that, for advanced PDAC patients, correcting elevated platelet count may bring about short-term survival benefit. However, as we recently found that thrombocytopenia can also cause deteriorated OS of PC, [ 17 ] the correction of thrombocytosis should be dealt with caution in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation